Rice to Sustainability: A systems thinking approach to advance sustainable rice - Edwards, Glory I. (Wageningen University & Research, 2023)
Rice is important for global food security, serving as a staple food for over half of the world's population. Rice production needs to increase to meet increasing global demands. However, rice production systems face many challenges in achieving sustainable growth related to environmental factors (such as soil quality, water and nutrient availability), national and international policy initiatives and socio-economic issues such as price spikes, labour scarcity and increased competition for arable land. Moreover, climate change adaptation, greenhouse gas emissions mitigations and the resilience of rice communities must be ensured. This grand challenge presents tensions between different objectives.